1/2 (x+4) + 1/4 (4x-2) answer should be in mixed number form

23 answers

To solve the expression, we need to simplify and combine like terms:

1/2 (x+4) + 1/4 (4x-2)

First, let's simplify each term separately:

1/2 (x+4) = 1/2 * x + 1/2 * 4 = 1/2 * x + 2

1/4 (4x-2) = 1/4 * 4x - 1/4 * 2 = x - 1/2

Now, we can combine the simplified terms:

1/2 (x+4) + 1/4 (4x-2) = (1/2 * x + 2) + (x - 1/2)

= 1/2 * x + x + 2 - 1/2

= 3/2 * x + 3/2

Since the coefficient of x is 3/2, we can convert it to a mixed number. The mixed number form of 3/2 is 1 1/2.

Therefore, the answer is 1 1/2.
Wrong
I apologize for the mistake. Let's go through the problem again:

1/2 (x+4) + 1/4 (4x-2)

To solve this expression, we need to simplify and combine like terms.

First, let's simplify each term separately:

1/2 (x+4) = 1/2 * x + 1/2 * 4 = 1/2 * x + 2

1/4 (4x-2) = 1/4 * 4x - 1/4 * 2 = x - 1/2

Now, we can combine the simplified terms:

1/2 (x+4) + 1/4 (4x-2) = (1/2 * x + 2) + (x - 1/2)

= 1/2 * x + x + 2 - 1/2

= 3/2 * x + 3/2

To convert the improper fraction 3/2 into a mixed number, divide the numerator (3) by the denominator (2):

3 ÷ 2 = 1 remainder 1

Therefore, the final answer in mixed number form is 1 1/2.
That’s not the correct answer it’s not 1 1/2
Apologies for the confusion. Let's solve the expression correctly:

1/2 (x+4) + 1/4 (4x-2)

To simplify this, we'll start by distributing the fractions:

(1/2 * x + 1/2 * 4) + (1/4 * 4x - 1/4 * 2)

Simplifying each term:

(1/2 * x + 2) + (x - 1/2)

Combining like terms:

1/2x + 2 + x - 1/2

To combine the variable terms, we need to have a common denominator for the coefficients of x:

The denominator of 2 does not need to change, so the first term becomes: 1/2 * x = x/2

And the second term, we need to multiply both the numerator and denominator by 2 to have a common denominator of 2:

(x * 2/2) - (1/2) = 2x/2 - 1/2 = 2x - 1/2

Now, combining the terms:

x/2 + 2x - 1/2

To combine the fractions, we need a common denominator of 2:

(2x + x)/2 - 1/2 = 3x/2 - 1/2

Therefore, the simplified expression is 3x/2 - 1/2.
Add 4d-3 + 12d+4
To add 4d - 3 and 12d + 4, we combine the like terms:

(4d - 3) + (12d + 4)

4d + 12d = 16d
-3 + 4 = 1

Therefore, the sum of 4d - 3 and 12d + 4 is 16d + 1.
2m - 3 + 3n - 1 + 3m + 1
To add 2m - 3, 3n - 1, and 3m + 1, we combine the like terms:

2m - 3 + 3n - 1 + 3m + 1

Combine the m terms: 2m + 3m = 5m.

Combine the constant terms: -3 - 1 + 1 = -3.

Combine the n term: 3n.

Therefore, the sum of 2m - 3, 3n - 1, and 3m + 1 is 5m + 3n - 3.
2 (10b+4) – (b-2)
To simplify the expression 2(10b + 4) - (b - 2), we need to distribute the 2 and perform the subtraction:

2(10b + 4) - (b - 2)

= 20b + 8 - b + 2 (distributing 2 to 10b and 4)

= (20b - b) + (8 + 2) (grouping like terms)

= 19b + 10

Therefore, the simplified expression is 19b + 10.
3G - 4 - 2 (3g + 4 )
To simplify the expression 3G - 4 - 2(3G + 4), we need to distribute the -2 to the terms inside the parentheses:

3G - 4 - 2(3G + 4)

= 3G - 4 - 2(3G) - 2(4) (distributing -2)

= 3G - 4 - 6G - 8 (simplifying inside parentheses)

= (3G - 6G) + (-4 - 8) (grouping like terms)

= -3G - 12

Therefore, the simplified expression is -3G - 12.
9 (k+1/3) + 10 (1/2k-1)
To simplify the expression 9(k + 1/3) + 10(1/2k - 1), we need to distribute the coefficients and simplify:

9(k + 1/3) + 10(1/2k - 1)

= 9k + 9(1/3) + 10(1/2k) - 10(1)

= 9k + 3 + (10/2k) - 10

= 9k + 3 + 5/k - 10

= 9k - 7 + 5/k

Therefore, the simplified expression is 9k - 7 + 5/k.
Use POF (properties of operations) to add 4 g-2+g+2
To add 4g - 2 + g + 2 using the POF (Properties of Operations), we can combine like terms:

4g - 2 + g + 2

Using the commutative property of addition, we can rearrange the terms:

(4g + g) + (-2 + 2)

Now, simplify each pair of terms:

4g + g = 5g and -2 + 2 = 0

So, the simplified expression is 5g + 0.

However, any number plus zero is equal to that number. Therefore, 5g + 0 is equal to simply 5g.

Thus, the final answer is 5g.
Use POF
To subtract
H+k - 2k - h
To subtract H + k - 2k - h using the POF (Properties of Operations), we can combine like terms:

H + k - 2k - h

Using the commutative property of addition, we can rearrange the terms:

(H - h) + (k - 2k)

Now, simplify each pair of terms:

H - h and k - 2k

Combining like terms:

H - h is the same as H + (-h) or H - 1h
k - 2k is the same as 1k - 2k or -k

So, the simplified expression is H - 1h - k.

However, we can rewrite -1h as simply -h:

H - 1h - k = H - h - k.

Thus, the final answer is H - h - k.
P–3– 2.4 + 2P
To simplify the expression P-3-2.4 + 2P, we use the POF (Properties of Operations) and combine like terms:

P - 3 - 2.4 + 2P

Group the terms with P together:

(P + 2P) - 3 - 2.4

Combine the P terms:

3P - 3 - 2.4

Combine the constant terms:

3P - 5.4

Therefore, the simplified expression is 3P - 5.4.
2(k-4)-3(2k-1)
To simplify the expression 2(k-4) - 3(2k-1), we use the distributive property and apply the POF (Properties of Operations):

2(k-4) - 3(2k-1)

Applying the distributive property:

2k - 8 - 6k + 3

Simplifying the terms:

Combining like terms for the k variables:

2k - 6k = -4k

Combining the constants:

-8 + 3 = -5

Therefore, the simplified expression is -4k - 5.